The phenomenon of reduplication in the Jacaru language. Interaction of phonology and morphology - Escobar Z., Emérita (2003)
One of the fields that summons researchers of Andean languages in Peru to continue exploring new data is related to morphophonological aspects. REDUPLICATION is one of them, since its nature involves the phonological aspect in interaction with the morphological aspect at the moment of word formation. Jacaru, one of the members of the Aru Family, presents the REDUPLICATION PHENOMENA - hereinafter referred to as (FR) - with morphophonemic characteristics that are peculiar or different from the other two most important Andean languages in Peru: Quechua and Aymara. Rather, it has similarities with some of the languages of the world that have also implemented this mechanism of lexical formation.